Analisis Pengendalian Persediaan Barang Fast Moving Dan Efisiensinya Dengan Menggunakan Metode Economic Order Quantity (EOQ): Studi Kasus Pada CV. X - Ayu Lupita Siva Alicia; Asaprima Putra Karunia; Meka Sabilla Salim; Nur Chayati (FISCAL: Jurnal Akuntansi dan Perpajakan, 2024)
In retail companies, inventory is an important component for the operation of the company. The purpose of this research is done to find out the inventory control system carried out by the company, inventory control analysis CV. X with the EOQ method, knowing the economical inventory cost and optimum purchase frequency with the EOQ method, and knowing the amount of safety stock and when will be reordered (reorder point) inventory items on CV. X. The type of research used is quantitative research with a descriptive approach. This analysis is carried out by comparing inventory control policies implemented by companies and inventory control using the EOQ method. The results of this research show that inventory control with the EOQ method can save total inventory costs of Rp 45,333,016 or 56% more efficient when compared to total inventory costs using company policies. In addition, the use of the EOQ method can produce optimal quantity and frequency of purchases as well as the application of safety stock and reorder points.Â